Incidence and risk factors of significant carotid artery stenosis in asymptomatic survivors of head and neck cancer after radiotherapy. Issue 2 (2nd April 2013) - Dorth, Jennifer A.; Patel, Pretesh R.; Broadwater, Gloria; Brizel, David M.
<x xml:space="preserve">Abstract</x> Background The incidence and risk factors of carotid artery stenosis in asymptomatic patients after head and neck radiation therapy (RT) are unknown. Methods This retrospective study reviewed asymptomatic patients treated with RT for head and neck cancer from 2000 to 2009 who underwent screening carotid ultrasound. Results Two hundred twenty‐four patients were included, the majority of whom had stage III to IV disease and received cisplatin‐based chemotherapy. Median time from RT completion to last carotid ultrasound was 3 years. Actuarial rate of carotid artery stenosis at 4 years was 14% (95% confidence interval [CI], 4% to 22%). Multivariate analysis revealed that carotid artery stenosis was associated with Framingham risk factors (hazard ratio [HR], 1.6 per factor; 95% CI, 1.2–2.2; p = .003). Among 135 patients treated with intensity‐modulated radiation therapy (IMRT), the HR for carotid artery stenosis was 1.4 for every 10 Gy increase in mean RT dose to the carotid bulb plus 2 cm (95% CI, 0.8–2.4; p = .35). Conclusion Prevention and screening programs should be considered for head and neck cancer survivors given the high risk of carotid artery stenosis. © 2013 Wiley Periodicals, Inc. Head Neck 36: 215–219, 2014